Laboratories based on internet : comparative analysis of current experiences and development of a virtual laboratory - Bottentuit Junior, João Batista (2006)
This paper introduces the concept, advantages and the development methodology of the virtual laboratories. It will be presented examples of usage of the virtual laboratories in an educational context as well as the conclusions of the comparative analysis of these projects. At the end it will be presented the virtual Organic Chemistry laboratory developed in Pontifica Universidade Católica do Rio Grande do Sul, which was the object of study of the research project developed by one of the researchers of this article. (Portuguese abstract) Esta comunicação apresenta o conceito, as vantagens e a metodologia de desenvolvimento dos laboratórios virtuais. Serão apresentados também alguns casos de utilização dos laboratórios virtuais em contexto educacional assim como as conclusões obtidas na análise comparativa desses projectos. Por último será apresentado o laboratório virtual de Química Orgânica desenvolvido na Pontifica Universidade Católica do Rio Grande do Sul que constituiu o objecto de estudo no projecto de pesquisa em desenvolvimento que trabalha um dos investigadores deste artigo.